Method for preparing electroactive material for metal ion battery
Patent Information
- Application Number
- JP2024173132
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-02-13
- Filing Date
- 2024-10-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2039-12-20
AI Technical Summary
は、実質的に、ミクロ細孔及びより小さなメソ細孔にシリコンを収容することによって得られる。
Smart Images

Figure 2025000925000001 
Figure 2025000925000002
Abstract
Description
[Technical field]
[0001] The present invention relates generally to electroactive materials suitable for use in electrodes for rechargeable metal-ion batteries, and more particularly to methods for making particulate materials having high electrochemical capacity suitable for use as anode active materials in rechargeable metal-ion batteries. [Background technology]
[0002] Rechargeable metal-ion batteries are widely used in portable electronic devices such as mobile phones and laptops, and are increasingly being applied in electric or hybrid vehicles. Rechargeable metal-ion batteries generally include an anode layer, a cathode layer, an electrolyte that transports metal ions between the anode and cathode layers, and an electrically insulating porous separator disposed between the anode and cathode. The cathode typically includes a metal current collector with a layer of metal ion containing metal oxide-based composite material, and the anode typically includes a metal current collector with a layer of electroactive material, defined herein as a material capable of inserting and releasing metal ions during charging and discharging the battery. For the avoidance of doubt, the terms "cathode" and "anode" are used herein in the sense that the battery is loaded such that the cathode is the positive electrode and the anode is the negative electrode. When the metal-ion battery is charged, metal ions are transported from the metal ion-containing cathode layer through the electrolyte to the anode and inserted into the anode material. The term "battery" is used herein to refer to both devices containing a single anode and a single cathode, and devices containing multiple anodes and / or multiple cathodes.
[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal-ion batteries. The use of lithium-ion batteries has already provided significant improvements over other battery technologies, but there is room for further development. To date, commercially available lithium-ion batteries have been primarily limited to the use of graphite as the anode active material. Upon charging a graphite anode, lithium is inserted between the graphite layers, resulting in a charge-discharge reaction with the empirical formula Li xC6, where x is greater than 0 and less than or equal to 1. As a result, graphite has a maximum theoretical capacity of 372 mAh / g in lithium-ion batteries, with practical capacities somewhat lower (approximately 340 mAh / g to 360 mAh / g). Other materials, such as silicon, tin, and germanium, can intercalate lithium at significantly higher capacities than graphite, but are not yet in widespread commercial use due to the difficulty of maintaining sufficient capacity over many charge-discharge cycles.
[0004] In particular, silicon has been recognized as a promising alternative to graphite in the manufacture of rechargeable metal-ion batteries with high gravimetric and volumetric capacities due to its extremely high capacity relative to lithium (see, for example, Non-Patent Document 1). Silicon has a theoretical maximum specific capacity of about 3600 mAh / g (Li ion battery) at room temperature. 15 However, the use of silicon as an anode material is complicated by its large volume change upon charging and discharging.
[0005] When lithium is intercalated into bulk silicon, the volume of the silicon material increases significantly, up to 400% of its original volume when the silicon is lithiated to its maximum capacity. Then, repeated charge-discharge cycles generate significant mechanical stresses in the silicon material, leading to fracture and delamination of the silicon anode material. The volumetric shrinkage of silicon particles upon delithiation can result in loss of electrical contact between the anode material and the current collector. To make matters even more difficult, the solid electrolyte interface (SEI) layer formed on the silicon surface is not mechanically durable enough to accommodate the expansion and contraction of silicon. As a result, the newly exposed silicon surface causes further decomposition of the electrolyte, an increase in the thickness of the SEI layer, and Lithium will be irreversibly consumed. Collectively, these failure mechanisms result in an unacceptable loss of electrochemical capacity over successive charge-discharge cycles.
[0006] Numerous approaches have been proposed to overcome the problems associated with the volume changes observed during charging of silicon-containing anodes. The most prevalent approach to address irreversible capacity loss in silicon-containing anodes is the use of some form of microstructured silicon as the electroactive material. It has been reported that fine silicon structures with cross sections less than about 150 nm, such as silicon films and silicon nanoparticles, are more resistant to volume changes during charging and discharging compared to silicon particles in the micron size range. However, none of these are particularly suitable for commercial scale application without morphology modification. Nanoscale particles are difficult to manufacture and handle, and silicon films do not provide sufficient bulk capacitance. For example, nanoscale particles tend to form agglomerates, which makes it difficult to effectively disperse the particles within the anode material matrix. The formation of nanoscale particle agglomerates also results in unacceptable capacity loss during repeated charge-discharge cycles.
[0007] It is also generally known that electroactive materials such as silicon can be deposited within the pores of porous support materials such as activated carbon materials. These composite materials offer some of the beneficial charge-discharge properties of nanoscale silicon particles while avoiding the difficulties of handling nanoparticles. For example, Guo et al. (Non-Patent Document 2) reported that porous carbon substrates are deposited with silicon particles uniformly distributed within the substrate's pore structure. discloses a silicon-carbon composite that provides a conductive scaffold with silicon nanoparticles stacked on top of each other. The formation of the SEI during the first charge cycle is confined to the remaining pore volume such that the remaining silicon is not exposed to the electrolyte during subsequent charge cycles. The composite shows improved capacity retention over multiple charge cycles, but the initial capacity in mAh / g of the composite is significantly lower than that for silicon nanoparticles.
[0008] US Patent Publication No. 2009 / 0133963 discloses an active material comprising a carbon-based scaffold having small pores branching off from a small number of larger pores. An electroactive material (e.g., silicon) is randomly located on the walls of both the large and small pores, as well as on the outer surface of the carbon-based scaffold.
[0009] It has been found that the performance of composite materials comprising a porous carbon scaffold and an electroactive material, such as silicon, located within the porous carbon scaffold can be optimized by using a porous carbon scaffold with a specific pore structure and a controlled ratio of electroactive material to available pore volume. For the desired end use of these composite materials in metal ion batteries, small particle size (e.g., D less than 20 μm) is essential. 50 ) are believed to be beneficial. However, it is difficult to produce these composite materials efficiently and consistently, especially on a large scale for commercial use. It is difficult to control the deposition of the electroactive material so that it deposits in the desired location within the pores of the porous carbon scaffold. It is also difficult to control the deposition when producing products with the desired small particle size. The present invention is directed to solving this problem.
[0010] Chemical vapor infiltration (CVI) is a process in which reactive gaseous precursors are used to infiltrate an additional phase into a porous substrate material. The porous substrate is placed on a perforated metal plate, and a mixture of carrier gas and gaseous precursors is passed through the porous substrate, which is held at an elevated temperature. The gaseous precursors chemically react at elevated temperatures within the pore structure of the substrate material and deposit on the inner surfaces of the pore spaces. The CVI process increases the density of the porous substrate material. CVI is particularly useful because the shape of the porous substrate is largely intact. Also, a high degree of uniformity can be achieved within the substrate by controlling the purity of the reactive gaseous precursors, as well as the pressure and temperature of infiltration.
[0011] It has been found that chemical vapor infiltration (CVI) can be used to deposit electroactive materials into microporous and / or mesoporous carbon materials with particle sizes less than 20 μm to produce composite materials with desired electrochemical properties. In the present invention, CVI refers in particular to the process of pyrolyzing a gaseous precursor of an electroactive material, such as silicon, on a surface, where the electroactive material is deposited in elemental form to form a gaseous by-product. The gaseous by-product can be deposited on the internal surfaces, in particular on the surfaces of the pore walls.
[0012] Typically, the low diffusivity of gaseous silicon precursors used in CVI of silicon compounds, or other gaseous precursors for other electroactive materials, into micro- and / or mesopore systems means that a kinetically limited (surface reaction limited) deposition regime must be used. However, this creates a number of problems from a processing standpoint. The main problem is that in large volume sample and reactor systems for high throughput / high volume and continuous processing, it is difficult to ensure the high thermal and mass transfer uniformity required to maintain a uniform deposition rate with respect to reactor location, processing time, and location of the particle pore system. It is therefore difficult to use CVI to deposit electroactive materials into the pores of porous carbon skeletons on a commercially useful scale. It is believed that there is no widespread commercial manufacturing route to process powders, especially in the size range below 20 μm, using CVI as a deposition technique.
[0013] Fluidized bed reactors (FBRs) can be used to carry out CVI. FBRs have wide application in the industry. FBRs provide a means of very efficient gas-solid contacting while providing uniform temperature distribution in the bed. This is achieved primarily by using gas flow to fluidize the particles and contact all surfaces with the reactive gas. FBRs meet many of the mass and heat transfer challenges mentioned above. Once fluidization is achieved, excellent solid-solid and gas-solid mixing is observed, especially when compared to alternative powder processing solutions for carrying out CVI such as fixed beds and rotary furnaces.
[0014] Particles can be divided into groups with respect to their size and density and with respect to their fluidization behavior. These groups are known as Geldart Group A, B, C, and D materials. Group A, B, and D materials can be fluidized with or without bubbling and slugging behavior, while Geldart C includes materials that are small in size and low in density and can be difficult to fluidize due to the presence of cohesive forces due to their small size. Carbon powders with small particle size can be considered Geldart Group C materials.
[0015] As described by Vahlas et al. in Non-Patent Document 3, FBR-chemical vapor deposition (CVD), including CVI, has been used to deposit a variety of catalytic metals and non-metals onto porous and non-porous materials.
[0016] However, carbon powders with sizes less than 20 μm tend to form large agglomerates when used in FBRs due to the strong interparticle cohesive forces at this length scale. This is problematic because fluidization of the individual particles may not occur, but only as large millimeter-sized agglomerates, leading to problems related to mass transfer rates within the agglomerates. Also, the carbon powder may not fluidize, and instead channeling (ratholing) may occur from locally applied shear forces in the gas flow that are insufficient to break down the cohesive forces between the particles (i.e., the gas passes around the powder bed instead of through it). For these reasons, FBRs have not been considered suitable for use in processes involving carbon powders with sizes less than 20 μm. [Prior art documents] [Patent documents]
[0017] [Patent Document 1] JP 2003-100284 A [Non-patent literature]
[0018] [Non-Patent Document 1] Insertion Electrode Materials for Rechargeable Lithium Batteries, Winter, M. et al. in Adv. Mater. 1998, 10, No. 10 [Non-Patent Document 2] Journal of Materials Chemistry A, 2013, pp. 14075-14079 [Non-Patent Document 3] Principles and applications of CVD powder technology, Materials Science and Engineering R53 (2006) 1-72 Summary of the Invention [Problem to be solved by the invention]
[0019] In this invention, chemical vapor infiltration into fluidized porous carbon powders allows for control of the kinetic and thermodynamic conditions of the infiltration reaction, ensuring that each porous carbon particle is exposed to a similar chemical and thermal environment. In essence, this invention treats individual micron-scale powders as mini-infiltration substrates, reducing the length scales characteristic of precursor diffusion and reaction, facilitating transfer to continuous processing for mass production. [Means for solving the problem]
[0020] In a first aspect, the present invention provides a method for producing a composition comprising the steps of: (a) containing micropores and / or mesopores and having a D of at least 20 μm 50 Providing a particulate porous carbon skeleton having a particle size; (b) depositing an electroactive material selected from silicon, tin, aluminum, germanium, and alloys thereof into the micropores and / or mesopores of the porous carbon skeleton using a chemical vapor infiltration process in a fluidized bed reactor to obtain intermediate particles; (c) grinding the intermediate particles to obtain composite particles; The present invention provides a method for making a particulate material comprising a plurality of composite particles, the method comprising:
[0021] Thus, the method of the present invention provides functional nanostructures containing electroactive materials by taking advantage of CVI to deposit electroactive materials within the pores of a porous carbon framework. The method also takes advantage of the use of FBR to perform CVI. The method provides a nanostructure having a D of at least 20 μm. 50 The use of particulate porous carbon skeletons with particle sizes as starting materials also avoids the difficulties of using FBR with carbon powders with small particle sizes. The milling step means that the method can be used to provide composite particles with reduced particle sizes compared to the starting materials, which may be useful for the desired end use in metal-ion batteries. In particular, composite particles in these size ranges are ideally suited for use in composite film negative electrodes (i.e., "anodes") for metal-ion batteries, as they are dispersible in slurries, structurally robust, and retain capacity over repeated charge-discharge cycles. Such composite films typically have thicknesses of less than 100 μm or less than 50 μm, with smaller particle sizes also aiding in achieving denser films of uniform thickness. Thus, the method of the present invention provides an effective way to make composite particles suitable for large-scale commercial use.
[0022] It may seem counterintuitive to use CVI in an FBR to create intermediate composite particles and then mill the intermediate particles. In particular, it has been thought that the milling step could damage the functional nanostructure of the intermediate particles obtained by the CVI process, i.e., the electroactive material deposited within the pores of the carbon skeleton. However, we show that milling can occur without significant levels of damage, since the breakage is on the relative μm length scale compared to the nm length scale of the functional units of the composite particles. It has been found that the carbon skeleton contains micropores and / or mesopores, so that desirable properties are retained in the product even upon milling.
[0023] In the methods of the present invention, the properties of the porous carbon skeleton starting material can be selected to impart a desired set of properties to the final product. For example, the porous carbon skeleton can be selected to have a particular pore structure, allowing the production of a product with a particular micropore and / or mesopore structure, since the milling step can occur without significant damage to the pore structure.
[0024] The electroactive material can be silicon or tin. The electroactive material is preferably silicon. The electroactive material can optionally include small amounts of one or more dopants. Suitable dopants include boron and phosphorus, other n-type or p-type dopants, or nitrogen. When silicon is the electroactive material, it can also be doped with small amounts of one or more other electroactive materials, such as tin, aluminum, and germanium. The dopants are preferably present in a total amount of 2% by weight or less, based on the total amount of the electroactive material and the dopant(s).
[0025] For the avoidance of doubt, the term "particle size" as used herein refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, where the volume of a particle is understood to include the volume of pores within the particle. 50 " and "D 50The term "particle size" refers to the median particle size on a volume basis, i.e., the diameter below which 50% by volume of the particle population lies. 10 " and "D 10 The term "particle size" refers to the 10th percentile median particle size on a volume basis, i.e., the diameter below which 10% by volume of the particle population lies. 90 " and "D 90 The term "particle size" refers to the volume-based 90th percentile median particle diameter, i.e., the diameter below which 90% of the particle population falls, by volume.
[0026] "D" is used herein to define particle size distribution. n The term "PD" is used herein to define pore size distribution. n " is to be distinguished from the term "PD n The general term "pore size" refers to the n-th percentile pore size based on volume relative to the total volume of micropores and mesopores. For example, as used herein, "D 50 The term "pore size" refers to the pore size below which 50% of the total micropore and mesopore volume, represented by P1, exists.
[0027] For the avoidance of doubt, any macropore volume (pore diameters greater than 50 nm) is not included in the PD n It is not taken into account for the purpose of calculating the value.
[0028] Particle size and size distribution can be determined by conventional laser diffraction techniques in accordance with ISO 13320:2009. Laser diffraction is based on the principle that particles scatter light at angles that vary with the size of the particle, and a collection of particles produces a scattered light pattern defined by intensity and angle that can be correlated to particle size distribution. Many laser diffraction instruments are commercially available for quickly and reliably determining particle size distribution. Unless otherwise stated, particle size distribution measurements defined or reported herein are based on conventional Malvern Instruments laser diffraction instruments. The particle size distribution was determined using a Malvern Mastersizer™ 3000 particle size analyzer, which works by projecting a helium neon gas laser beam through a transparent cell containing the particles of interest suspended in an aqueous solution. The light striking the particles is scattered at angles inversely proportional to the particle size, and a photodetector array measures the light intensity at a number of predefined angles, and the intensities measured at the various angles are processed by a computer using standard theoretical principles to determine the particle size distribution. The laser diffraction values reported herein are obtained using a wet dispersion of the particles in distilled water. The refractive index of the particles is 3.50 and the refractive index of the dispersant is 1.33. It is assumed to be 0. The particle size distribution is calculated using the Mie scattering model.
[0029] Porous Carbon Skeleton The porous carbon skeleton has a D of at least 20 μm. 50 The porous carbon skeleton can be easily used in FBRs. The porous carbon skeleton can have a particle size of 20 μm to 1000 μm, or 30 μm to 500 μm, or 60 μm to 150 μm. 50 The porous carbon skeleton optionally has a particle size of at least 30 μm, at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm, or at least 80 μm. 50 The porous carbon skeleton optionally has a particle size of 1000 μm or less, or 500 μm or less, or 250 μm or less, or 150 μm or less, D 50 It has a particle size.
[0030] The porous carbon skeleton optionally has a D of at least 5 μm, at least 15 μm, at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm. 10 Particle size: D 10 Maintaining the particle size above these values advantageously avoids the presence of numerous carbon skeletons with small particle sizes that may be unsuitable for an FBR.
[0031] The porous carbon skeleton optionally has a D of 1500 μm or less, or 1000 μm or less, or 750 μm or less, or 500 μm or less, or 200 μm or less. 90 The porous carbon skeleton optionally has a particle size of 1550 μm or less, or 1050 μm or less, or 800 μm or less, or 550 μm or less, or 250 μm or less. 98 Particle size: D 90 Particle size and / or D 98 Maintaining particle sizes below these values advantageously avoids the presence of numerous carbon skeletons with larger particle sizes that may not be suitable for CVI.
[0032] For example, the porous carbon skeleton has a D of at least 15 μm. 10 Particle size, D of at least 20 μm 50 Particle size and D below 200 μm 90 The porous carbon skeleton can have a particle size of at least 5 μm. 10 Particle size, D in the range of 20μm to 250μm 50 Particle size, D below 750 μm 90 Particle size and D below 1000 μm 98 The porous carbon skeleton can have a particle size of at least 5 μm. 10 Particle size, D in the range of 20μm to 200μm 50 Particle size, D below 500 μm 90 Particle size and D below 800 μm 98 The porous carbon skeleton can have a particle size of at least 40 μm. 10 Particle size, D in the range of 60μm to 150μm 50 Particle size and D below 200 μm 90 Particle size and D below 250 μm 98 It can have a particle size.
[0033] The porous carbon skeleton preferably has a narrow particle size distribution span. For example, the particle size distribution span (D 90 -D 10 ) / D 50(defined as) is preferably 5 or less, more preferably 4 or less, more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By maintaining a narrow particle size distribution span, a steady deposition of the electroactive material within the pores of the carbon skeleton can be more easily achieved.
[0034] The porous carbon framework preferably comprises a three-dimensionally interconnected open pore network comprising a combination of micropores and / or mesopores, and optionally a small amount of macropores. In accordance with IUPAC nomenclature, the term "micropores" is used herein to refer to pores with a diameter of less than 2 nm, the term "mesopores" is used herein to refer to pores with a diameter of 2 nm to 50 nm, and the term "macropores" is used herein to refer to pores with a diameter of more than 50 nm.
[0035] Any reference herein to the volume of micropores, mesopores, and macropores within a porous carbon skeleton, as well as to the pore volume distribution within a porous carbon skeleton, is intended to be taken as meaning the volume of the micropores, mesopores, and macropores alone (i.e. "Porous carbon framework" refers to the internal pore volume of a porous carbon framework in the absence of electroactive material or other materials occupying some or all of the pore volume.
[0036] In this specification, the volume fraction of micropores (relative to the total volume of micropores and mesopores) is denoted by the symbol φ a The volume fraction of mesopores (relative to the total volume of micropores and mesopores) is represented by the symbol φ b Since it is expressed as a +φ b It will be understood that =1.
[0037] Porous carbon frameworks are characterized by a pore volume in the form of micropores and / or mesopores. As used herein, the total volume of micropores and mesopores (i.e., the total pore volume in the range of 0 nm to 50 nm) is defined as P1cm 3 / g, where P1 represents a dimensionless whole number. The value of P1 is also used to correlate the effective pore volume in the porous carbon scaffold with the weight ratio of electroactive material to the porous carbon scaffold in the final product.
[0038] For the avoidance of doubt, P1 as used herein relates to the pore volume of the porous carbon skeleton when measured alone, i.e., in the absence of silicon or other material occupying the pores of the porous carbon skeleton. Similarly, any references herein to the volume of micropores, mesopores, and macropores in the porous carbon skeleton, as well as any references to the distribution of pore volume within the porous carbon skeleton, refer to the internal pore volume of the porous carbon skeleton alone (i.e., in the absence of silicon or other material occupying the pore volume).
[0039] P1 can have a value in the range of 0.4 to 2.5. Thus, the porous carbon skeleton has a density of at least 0.4 cm 3 / g and up to 2.5cm 3 / g of pore volume.
[0040] P1 may have a value in the range of 0.4 to 0.6, which corresponds to a small pore volume in the form of micropores and / or mesopores.
[0041] Alternatively, P1 can have a value of at least 0.6, or at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.2. The use of a high porosity carbon skeleton is advantageous as it allows more silicon to be accommodated within the pore structure, and it has been found that a high porosity carbon skeleton, whose pore volume is primarily in the form of micropores and smaller mesopores, has sufficient strength to accommodate the volumetric expansion of the electroactive material without the porous carbon skeleton breaking or otherwise degrading.
[0042] P1 may have a value of 2.5 or less, or 2.2 or less, or 2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less, or 1.2 or less. The internal pore volume of the porous carbon scaffold is preferably limited at a value where the increased fragility of the porous carbon scaffold outweighs the benefits of increased pore volume to accommodate greater amounts of electroactive material.
[0043] The value of P1 can be in the range of 0.4 to 2.5, or in the range of 0.6 to 2.5, or in the range of 0.7 to 2, or in the range of 0.7 to 1.2.
[0044] Micropore volume fraction (φ a ) can be at least 0.1, or in the range of 0.1 to 0.9. a is preferably greater than 0.5, more preferably greater than 0.6, more preferably greater than 0.7, more preferably greater than 0.8.
[0045] A pore fraction with a diameter in the range of larger mesopores can be advantageous as it facilitates electrolyte access to the electroactive material in the final product. Pores having diameters in the nm range (i.e., larger mesopores) can optionally constitute at least 1%, at least 2%, at least 5%, or at least 10% of the total micropore and mesopore volume of the porous carbon skeleton.
[0046] The pore size distribution of the porous carbon skeleton can be unimodal, bimodal, or multimodal. The term "pore size distribution" as used herein refers to the distribution of pore sizes relative to the cumulative total internal pore volume of the porous carbon skeleton. A bimodal or multimodal pore size distribution may be preferred since the proximity of the smallest pores to larger diameter pores provides the advantage of efficient transport of ions through the porous network to the electroactive material. Composite particles made from the porous carbon skeleton therefore have high ion diffusivity and therefore improved rate performance.
[0047] Preferably, the bimodal or multimodal pore size distribution comprises a peak pore size in the micropore range and a peak pore size in the mesopore range, which differ from each other by 5 to 20 times, more preferably about 10 times. For example, the porous carbon skeleton can have a bimodal pore size distribution having a peak at 1.5 nm and a peak at 15 nm. The porous carbon skeleton can have a bimodal pore size distribution having a peak at 2 nm and a peak at 20 nm. The porous carbon skeleton can have a bimodal pore size distribution having a peak at 1.2 nm and a peak at 12 nm.
[0048] The total volume of micropores and mesopores, as well as the pore size distribution of micropores and mesopores, were determined using quenched solid-state density functional theory (QSDFT) at 77 K for 10°C according to standard methodologies specified in ISO 15901-2 and ISO 15901-3. -6 The pore volume and pore size distribution are determined using nitrogen gas adsorption up to a relative pressure of p / p0. Nitrogen gas adsorption is a technique for characterizing the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure is increased, the gas condenses initially in the pores with the smallest diameter, until a saturation point is reached where all pores are filled with liquid. The nitrogen gas pressure is then reduced in steps to allow the liquid to evaporate from the system. The pore volume and pore size distribution can be determined by analysis of the adsorption and desorption isotherms and the hysteresis between them. Suitable devices for measuring the pore volume and pore size distribution by nitrogen gas adsorption include the TriStar II Porosity Analyzer and the TriStar II Plus porosity analyzer, as well as the Autosorb IQ porosity analyzer available from Quantachrome Instruments.
[0049] Nitrogen gas adsorption is effective for measuring the pore volume and pore size distribution of pores with diameters up to 50 nm, but is less reliable for pores with much larger diameters. Therefore, for the purposes of the present invention, nitrogen adsorption is used to determine the pore volume and pore size distribution of only pores with diameters of 50 nm or less. As mentioned above, the value of P1 is determined considering only pores with diameters of 50 nm or less (i.e., only micropores and mesopores), and similarly, the value of PD n , and φ a , φ b , φ 20 , φ 10 The values of φ, and φ (discussed below) are determined for the total volume of micropores and mesopores only.
[0050] Given the limitations of available analytical techniques, it is not possible to use a single technique to measure the pore volume and pore size distribution across the full range of micropores, mesopores, and macropores. When the porous carbon skeleton contains macropores, the volume of pores in the range above 50 nm and up to 100 nm is referred to herein as P2cm. 3 / g and is measured by mercury intrusion porosimetry. The value of P2 relates to the pore volume of the porous carbon skeleton when measured alone, i.e., in the absence of electroactive or other material occupying the pores of the porous carbon skeleton.
[0051] For the avoidance of doubt, the value of P2 is taken for pores with diameters of more than 50 nm to 100 nm. Only the volume of macropores up to 100 nm in diameter is considered; that is, the value of P2 includes only the volume of macropores up to 100 nm in diameter. Any pore volume measured by mercury porosimetry at pore diameters of 50 nm or less is disregarded for purposes of determining the value of P2. Pore volume measured by mercury porosimetry above 100 nm is assumed to be interparticle porosity for purposes of the present invention, and this pore volume is also not considered when determining the value of P2. As mentioned above, nitrogen adsorption is used to characterize mesopores and micropores.
[0052] Mercury intrusion porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying various levels of pressure to a sample of the material immersed in mercury. The pressure required to force mercury into the pores of the sample is inversely proportional to the pore size. Mercury intrusion values reported here were obtained according to ASTM UOP578-11, with a surface tension of mercury at room temperature, γ, of 480 mN / m, and a contact angle, φ, of 140°. The density of mercury at room temperature is 13.5462 g / cm 3 There are many high-precision mercury intrusion instruments available commercially, such as the AutoPore IV series of automated mercury intrusion meters available from Micromeritics Instrument Corporation, USA. For a complete review of mercury intrusion methods, refer to "Analytical Methods in Fine Particle Technology, 1997, Micromeritics Instrument Corporation" by PA Webb and C. Orr (ISBN 0-9656783-0).
[0053] The volume of the macropores (i.e., the value of P2) is preferably small compared to the volume of the micropores and mesopores (i.e., the value of P1). Although some of the macropores may be useful to facilitate electrolyte access to the pore network, the advantages of the present invention are obtained substantially by containing the silicon in the micropores and smaller mesopores.
[0054] Thus, according to the present invention, the total volume of macropores in the porous carbon skeleton is determined by mercury intrusion porosimetry (P2cm 3 / g, where P2 preferably has a value of 0.2×P1 or less, or 0.1×P1 or less, or 0.05×P1 or less, or 0.02×P1 or less, or 0.01×P1 or less, or 0.005×P1 or less.
[0055] In preferred embodiments, P2 has a value of 0.3 or less, or 0.25 or less, or 0.20 or less, or 0.15 or less, or 0.1 or less, or 0.05 or less. As discussed above in relation to larger mesopores, a small pore volume fraction in the macropore range can be advantageous to facilitate electrolyte access to the electroactive material in the final product.
[0056] The open pore network optionally includes a hierarchical pore structure, ie, a pore structure in which smaller pores branch off from larger pores and the pore sizes have some order.
[0057] It will be understood that intrusion techniques such as gas adsorption and mercury porosimetry are only effective for determining the pore volume of pores accessible to nitrogen or mercury from the exterior of the porous carbon skeleton. The porosity values (P1 and P2) defined herein are understood to refer to the volume of open pores, i.e., pores accessible to fluids from the exterior of the porous carbon skeleton. Completely enclosed pores that cannot be identified by nitrogen adsorption or mercury porosimetry are not considered in defining the porosity values herein. Similarly, any pore volume located within pores small enough to be below the detection limit by nitrogen adsorption is not considered in determining the value of P1.
[0058] The porous carbon skeleton may comprise crystalline or amorphous carbon, or a mixture of amorphous and crystalline carbon. The porous carbon skeleton may be either a hard or soft carbon skeleton, and may suitably be obtained by known procedures, including pyrolysis of polymers or organics.
[0059] As used herein, the term "hard carbon" refers to carbon atoms that are primarily distributed in nanoscale polyaromatic domains. 2 It refers to a disordered carbon matrix that adopts a hybridized (three-way bond) state. The polyaromatic domains are cross-linked by chemical bonds, e.g., COC bonds. Because the polyaromatic domains are chemically cross-linked, the hard carbon cannot be converted to graphite at high temperatures. The high G band (approx. 1600 cm) in the Raman spectrum-1 ), hard carbon has graphite-like properties. However, the high D band in the Raman spectrum (approximately 1350 cm -1 ), carbon is not entirely graphite-like.
[0060] The term "soft carbon" as used herein also refers to carbon atoms that are primarily dispersed in polyaromatic domains having dimensions in the range of 5 nm to 200 nm. 2 It refers to a disordered carbon matrix that adopts a hybridized (three-way bond) state. In contrast to hard carbon, the polyaromatic domains in soft carbon are not cross-linked by chemical bonds but are held together by intermolecular forces; that is, at high temperatures, soft carbon can be graphitized. The porous carbon skeleton preferably has at least 50% sp 2 For example, the porous carbon skeleton preferably contains 50% to 98% sp 2 Hybrid carbon, 55%-95% sp 2 Hybrid carbon, 60%-90% sp 2 Hybrid carbon, or 70% to 85% sp 2 It may contain hybridized carbon.
[0061] A variety of different materials can be used to create suitable porous carbon scaffolds. Examples of organic materials that can be used include plant biomass, including lignocellulosic materials (coconut shells, rice husks, wood, etc.), and fossil carbon sources such as coal. Examples of polymeric materials that form porous carbon scaffolds upon pyrolysis include phenolic resins, novolac resins, pitch, melamine, polyacrylates, polystyrene, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and various copolymers that contain monomer units of acrylates, styrene, α-olefins, vinylpyrrolidone, and other ethylenically unsaturated monomers. Depending on the starting materials and the conditions of the pyrolysis process, a variety of different hard carbon materials are available in the art.
[0062] To increase the mesopore and micropore volume, the porous carbon framework can be subjected to a chemical or gas activation process. Suitable activation processes include contacting the pyrolyzed carbon with one or more of oxygen, steam, CO, CO2, and KOH at temperatures ranging from 600°C to 1000°C.
[0063] Mesopores can also be obtained by known templating processes using extractable pore formers such as MgO and other colloidal or polymeric templates, which can be removed by thermal or chemical means after pyrolysis or activation.
[0064] The porous carbon skeleton is preferably at least 750 mm 2 / g, or at least 1000m 2 / g, or at least 1250m 2 / g, or at least 1500m 2 / g. The term "BET surface area" as used herein is taken to refer to the surface area per unit mass calculated from measurements of the physical adsorption of gas molecules on a solid surface using the Brunauer-Emmett-Teller theory according to ISO 9277. Preferably, the BET surface area of the conductive porous particle scaffold is greater than 4000 m 2 / g or less, or 3500m 2 / g or less, or 3250m 2 / g or less, or 3000m 2 / g or less.
[0065] As mentioned above, the inventors have found that the carbon skeleton contains micropores and / or mesopores so that the desired properties are retained in the product even after grinding. Thus, the present invention allows the desired properties of the composite particulate product to be targeted by controlling the pore structure of the porous carbon skeleton. Certain classes of porous carbon skeletons are described below and are used in the present invention. The porous carbon scaffolds described herein may be utilized in a variety of ways to provide certain classes of composite particle products. It will be understood that the characteristics of the classes of porous carbon scaffolds described below should be considered in combination with the characteristics of the porous carbon scaffolds described above, such as particle size.
[0066] Porous carbon skeleton 1 The porous carbon skeleton 1 has a P1 value of at least 0.5 and a PD of 5 nm or less. 50 It is characterized by the pore size.
[0067] The value of P1 is preferably at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, such as at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2.
[0068] The value of P1 can be up to 2.5. The value of P1 can be preferably 2.2 or less, or 2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less, or 1.2 or less, or 1.1 or less, or 1.0 or less, or 0.9 or less. The value of P1 is more preferably 1.2 or less, or 1.1 or less, or 1.0 or less, or 0.9 or less.
[0069] The value of P1 can preferably be, for example, in the range of 0.7 to 1.5, or in the range of 0.75 to 1.4, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0070] PD of porous carbon framework 1 50 The pore size is preferably 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less. 50The pore size is preferably at least 0.8 nm, or at least 1 nm, or at least 1.2 nm. It is therefore particularly preferred that 50% or more of the total micropore and mesopore volume is in the form of micropores.
[0071] More preferably, at least 80% of the total micropore and mesopore volume of the porous carbon skeleton 1 has a pore morphology with a diameter of 5 nm or less. 80 The pore size is preferably 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less.
[0072] The volume of larger mesopores in the porous carbon skeleton 1 is preferably PD 90 The pore size is restricted to be 20 nm or less, or 15 nm or less, or 12 nm or less, or 10 nm or less, or 8 nm or less, or 6 nm or less, or 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less.
[0073] Preferably, PD 95 The pore size is 20 nm or less, or 15 nm or less, or 12 nm or less, or 10 nm or less.
[0074] Porous carbon skeleton 2 The porous carbon skeleton 2 has a P1 value of at least 0.6 and a micropore volume fraction φ in the range of 0.1 to 0.9. a It is characterized by:
[0075] The porous carbon skeleton 2 is also characterized by a pore volume that is substantially skewed towards smaller pores, such that a minimum of 75% of the total micropore and mesopore volume has the morphology of pores having diameters of 20 nm or less. The volume fraction of pores with diameters of 20 nm or less (relative to the total volume of pores) is denoted by φ 20 and the symbol φ 10 and φ5 are used to define the volume fractions corresponding to pores with diameters less than or equal to 10 nm and less than or equal to 5 nm, respectively.
[0076] The value of P1 is preferably at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1. P1 can optionally be at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2. The value of P1 can be up to 2.2. The value of P1 is more preferably 2.2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less, or 1.2 or less.
[0077] The value of P1 can preferably be, for example, in the range of 0.6 to 1.4, or in the range of 0.65 to 1.4, or in the range of 0.7 to 1.4, or in the range of 0.75 to 1.4, or in the range of 0.6 to 1.3, or in the range of 0.65 to 1.3, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.6 to 1.2, or in the range of 0.65 to 1.2, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.6 to 1, or in the range of 0.65 to 1, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.6 to 0.9, or in the range of 0.65 to 0.9, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0078] φ a The value of φ is preferably in the range of 0.15 to 0.85, more preferably in the range of 0.2 to 0.8. In some embodiments, to take advantage of the high capacity retention due to the very fine nanostructure of the electroactive material located within the micropores, φ a is preferably in the range of 0.45 to 0.85, or in the range of 0.5 to 0.8, or in the range of 0.6 to 0.8. In other cases, particularly to take advantage of the opportunities for high loadings of electroactive material, φ a is preferably in the range of 0.2 to 0.5, or in the range of 0.3 to 0.5.
[0079] φ 20is preferably at least 0.8, more preferably at least 0.85, more preferably at least 0.9.
[0080] φ for the total volume of micropores and mesopores 10 is preferably at least 0.75, or at least 0.8, or at least 0.85. φ5 relative to the total volume of micropores and mesopores is preferably at least 0.75, or at least 0.8, or at least 0.85. Thus, at least 75% of the total micropore and mesopore volume of the porous carbon scaffold preferably has a pore morphology with a diameter of 10 nm or less, more preferably 5 nm or less.
[0081] Porous Carbon Skeleton 3 The porous carbon skeleton 3 has a P1 value of at least 0.6 and a PD of 2 nm or less. 50 It is characterized by the pore size.
[0082] The value of P1 is preferably at least 0.75, or at least 0.8, or at least 0.85. P1 can optionally be at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2. The value of P1 can usually be 2.5 or less. The value of P1 is more preferably 2.4 or less, or 2.2 or less, or 2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less, or 1.2 or less, or 1.1 or less, or 1.0 or less, or 0.9 or less.
[0083] The value of P1 can preferably be, for example, in the range of 0.6 to 1.4, or in the range of 0.65 to 1.4, or in the range of 0.7 to 1.4, or in the range of 0.75 to 1.4, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.7 to 1, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0084] PD of porous carbon framework 3 50 The pore size is preferably 1.8 nm or less, or 1.6 nm or less, or 1.4 nm or less, or 1.2 nm or less, or 1 nm or less.
[0085] Preferably, at least 80% of the total micropore and mesopore volume of the porous carbon skeleton 3 has a pore morphology with a diameter of 5 nm or less. 80 The pore size is preferably 5 nm or less, or 4.5 nm or less, or 4 nm or less, or 3.5 nm or less, or 3 nm or less, or 2.5 nm or less, or 2.2 nm or less, or 2 nm or less, or 1.8 nm or less, or 1.6 nm or less.
[0086] PD 90 The pore size is preferably 10 nm or less, or 8 nm or less, or 6 nm or less, or 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less.
[0087] PD 95 The pore size is preferably 15 nm or less, or 12 nm or less, or 10 nm or less.
[0088] CVI / FBR A laboratory-scale FBR can be used to contact the porous carbon skeleton with a gas mixture containing a gaseous precursor of the electroactive material (e.g., silane) to deposit the electroactive material in the micropores and / or mesopores of the skeleton by CVI. As an inert fluidizing gas, nitrogen gas can be used, but other inert gases such as argon, hydrogen, or helium can also be used. It will be understood that in the method of the present invention, the porous carbon skeleton is fluidized in an FBR.
[0089] The method of the present invention employs CVI of a gaseous precursor of an electroactive material into the pore structure of a porous carbon skeleton, the gaseous precursor preferably being a silicon-containing gas.
[0090] Suitable silicon-containing precursors include silane (SiH4), disilane (Si2H6), trisilane (Si3H8), tetrasilane (Si4H 10 ), or chlorosilanes such as trichlorosilane (HSiCl3), or methylchlorosilanes such as methyltrichlorosilane (CH3SiCl3) or dimethyldichlorosilane ((CH3)2SiCl2). The silicon-containing precursor is preferably a silane.
[0091] The CVI process can also utilize gaseous precursors of the dopant material to deposit the doped electroactive material within the micropores and / or mesopores of the porous carbon skeleton. When the dopant is boron, suitable precursors include borane (BH3), triisopropyl borate ([(CH3)2CHO]3B), triphenylborane ((C6H5)3B), and tris(pentafluorophenyl)borane ((C6F5)3B), preferably borane. When the dopant is phosphorus, the suitable precursor is phosphine (PH3).
[0092] The precursors can be used either in pure form or, more commonly, as a dilute mixture with an inert carrier gas such as nitrogen or argon. For example, the precursors can be present in an amount of 0.5% to 20% by volume, or 10% by volume, based on the combined volume of the precursor and the inert carrier gas. The CVI process is preferably carried out at a total pressure below atmospheric pressure (101.3 kPa) (e.g., in the range of 50 kPa to 101.3 kPa) with a low partial pressure of the gaseous precursor, and the remaining partial pressure is maintained at atmospheric pressure using an inert padding gas such as hydrogen, nitrogen, or argon. It becomes pressure.
[0093] The temperature of the CVI process is selected such that the precursor is pyrolyzed to the electroactive material. The CVI process is suitably carried out at a temperature in the range of 200°C to 1250°C, or in the range of 400°C to 700°C, or in the range of 400°C to 600°C, or in the range of 400°C to 550°C, or in the range of 450°C to 550°C, or in the range of 450°C to 500°C. The CVI process is preferably carried out at a temperature in the range of 400°C to 500°C, preferably in the range of 400°C to 450°C or in the range of 450°C to 500°C. The CVI process is preferably carried out at or above the minimum fluidization velocity (Umf) of the particulate material. The superficial velocity is preferably greater than the minimum fluidization velocity (Umf) of the particulate material. The minimum fluidization velocity (Umf) is a quantity that is typically measured, the value of which varies with particle size, particle density, and gas viscosity. The minimum fluidization velocity defines the flow rate of gas that must be fed into the reactor vessel to achieve a velocity that will entrain the particles into a "fluid-like" state. The flow rate in a CVI process is preferably selected to provide good solid-solid and solid-gas mixing and minimize particle carryover from the reactor. The CVI process is preferably carried out in the range of 1 to 20 times the minimum fluidization velocity (Umf).
[0094] Without wishing to be bound by theory, it is believed that controlling the particle size of the porous carbon scaffold in the manner described above provides kinetic control of the infiltration of the electroactive material. Kinetic control of the infiltration is believed to result in composite particles with a uniform distribution of the electroactive material throughout. This can lead to pore blockage throughout the volume of the scaffold after a certain amount of electroactive material is deposited. Controlling the particle size of the porous carbon scaffold has the advantage of allowing high infiltration efficiency in the temperature and concentration ranges used in the CVI process, and also makes the scaffold suitable for fluidization in the classical sense (such as Geldert's A group).
[0095] Crushing The method of the invention includes a step of milling the intermediate particles to obtain said composite particles. The milling step is performed such that the particle size of the composite particles is smaller than the particle size of the particulate porous carbon scaffold. An advantage of the invention is that the milling step provides a final product with a small particle size suitable for use in metal ion batteries while enabling the use of CVI in FBRs, a process suitable for large scale commercial use.
[0096] During the CVI process in the FBR, there may be some aggregation of the porous carbon skeleton, and therefore the particle size of the intermediate particles may be larger than that of the porous carbon skeleton.
[0097] The grinding can be carried out by various types of grinding equipment, such as mills such as wet mills, ball mills, jet mills, high shear stirring devices, ultrasonic devices, etc. Considering the reactivity of the intermediate particles immediately after infiltration is completed, the grinding is preferably carried out by dry mills, since the electroactive materials deposited by the CVI process may be reactive. For example, silicon deposited from silane contains a significant amount of Si-H bonds. These bonds are reactive towards organic molecules and water. Therefore, the presence of oxygen or organic solvents can cause an exothermic reaction, leading to partial destruction of the Si / C composite and / or degradation to a quality lower than that required for commercial metal-ion battery materials.
[0098] Among dry mills, jet mills are preferred due to their ability to reduce particle size. Jet mills use high velocity jets of compressed air or inert gas to grind particles. Jet mills can be used with starting materials having sizes up to about 1 mm, and are known to readily achieve sizes on the order of 1 μm with relatively little energy input.
[0099] There are different types of jet mills, for example, rotary (rotating motion) and flowing opposed jet. Rotary uses tangential gas forces from the wall to accelerate the particles. Flowing opposed jet works by multiple jets separated at equal angles to each other, colliding the particles on opposing collision trajectories. Flowing opposed jet mills are more suitable when higher capacities are desired. The grinding action is achieved in both types of mills by particle-particle collisions, not by collisions with a hard object. This particular mode of action results in a grind with a narrow particle size distribution, which is beneficial for incorporation into electrodes of metal-ion batteries. Also, the use of an inert grinding gas with controlled composition (limited oxygen and moisture content) results in a high grind purity.
[0100] Either rotary jet mills (e.g., spiral jet mills) or fluidized opposed jet mill designs can be used with diameters from 0.04 m up to several meters, grinding gas pressures of 50 kPa to 1000 kPa, and a maximum starting particle size of 1 mm. The grinding gas is either an inert gas such as nitrogen or argon, or a mixture of these with low partial pressures of air, water, or oxygen.
[0101] The ground particles can optionally be classified by size, for example by centrifugation or sieving.
[0102] Prior to the milling step, the intermediate particles can be passivated. That is, the particle surface can be treated to reduce its chemical reactivity, preferably to minimize or prevent further oxidation of the particle surface in subsequent process steps or handling. For example, the intermediate particles can be passivated in a low oxygen concentration environment, such as an oxygen concentration of less than 10% by volume. An inert gas, such as nitrogen, can be used to passivate the intermediate particles. A gas mixture with a low oxygen concentration can also be used. Passivation of the intermediate particles has the advantage that undesired further reactions of the intermediate particles are suppressed. For example, passivation of the intermediate particles can remove reactive Si-H bonds. This helps to maintain the structure of the electroactive material deposited in the pores of the porous carbon skeleton from the CVI process. This is beneficial when the composite particles are used in metal-ion batteries. The milling step can also be performed in a low oxygen concentration environment, such as an inert gas or a gas mixture with a low oxygen concentration. The milling step can be conveniently performed in the same atmosphere as any passivation step.
[0103] Prior to the grinding step, optionally in combination with a passivation step, the intermediate particles can be cooled. Cooling can be performed to a temperature below 100° C. or below 50° C., or to ambient temperature. Cooling the intermediate particles has the advantage that it makes it easier to transfer the intermediate particles to a grinding device.
[0104] The process of the present invention can be a continuous or batch process. In a continuous process, the passivation and cooling steps must be carried out in a vessel separate from the FBR. The vessel separate from the FBR can be a grinding unit.
[0105] Composite particle products It is an advantage of the present invention that the properties of the composite particle product can be controlled by selecting the properties of the porous carbon skeleton starting material, since the inventors have found that crushing can occur without significant levels of damage, since the breakage is on the relative μm length scale compared to the nm length scale of the functional units of the composite particle. In other words, the milling process provides the composite particle product with the desired particle size while maintaining the desired nanostructure resulting from depositing the electroactive material into a porous carbon scaffold containing micropores and / or mesopores using CVI. For example, both the intermediate and composite particles can include multiple nanoscale domains of elemental form of electroactive material located within the micropores and / or mesopores of the porous carbon scaffold. The term "nanoscale domain" as used herein refers to the nanoscale bodies of electroactive material located within the pores of the porous carbon scaffold. The maximum dimension of the nanoscale silicon domain is defined by the pore size of the pore in which the silicon is located.
[0106] Composite particles are generally particulate materials having nanoscale domains of electroactive material in a porous carbon framework having a pore volume that includes micropores and / or mesopores. This particle structure has been found to provide electroactive materials with very high gravimetric and volumetric capacities upon lithiation and high reversible capacity retention over multiple charge / discharge cycles.
[0107] Without being bound by theory, it is believed that the location of the nanoscale electroactive domains within the micropores and / or mesopores provides, first, fine electroactive structures that can be lithiated and delithiated without excessive structural stress. It is believed that these very fine electroactive domains are less resistant to elastic deformation and more resistant to fracture than larger electroactive structures. By allowing a relatively high percentage of the pore volume to be occupied by the electroactive material, the composite particles can have high capacity. Furthermore, the location of the nanoscale electroactive domains within the micropores and / or mesopores limits the formation of SEI, since only a small area of the electroactive surface is accessible to the electrolyte.
[0108] In some cases, composite particles produced by the present invention may include pores that are completely enclosed and covered by the electroactive material such that the voids are not accessible to the electrolyte.
[0109] The particle size of the composite particles can be targeted by controlling the grinding process, and optionally the process of classifying the particles by size, to provide the desired particle size distribution in the end use application.
[0110] As a result of the grinding of the intermediate particles in step (c), the composite particles D 50 The particle size is the D 50 Therefore, the composite particles obtained in step (c) have a D 50 As far as particle sizes go, e.g. up to 50 μm D 50 The composite particles can have a particle size of, for example, 40 μm or less, or 30 μm or less, or 25 μm or less, D 50 It can have a particle size.
[0111] Composite particles have a D of 20 μm or less. 50 For example, the composite particles may have a particle size of 15 μm or less, or 12 μm or less, or 10 μm or less, or 9 μm or less, or 8 μm or less, or 7 μm or less, or 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less, or 3.5 μm or less. 50 It can have a particle size.
[0112] The composite particles have a D of at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. 50 It can have a particle size.
[0113] The composite particles are preferably in the range of 0.5 μm to 20 μm, or in the range of 0.5 μm to 15 μm, or in the range of 0.5 μm to 12 μm, or in the range of 0.5 μm to 10 μm, or in the range of 0.5 D in the range of 0.5μm to 8μm, or 0.5μm to 9μm, or 0.5μm to 7μm 50Composite particles within these size ranges and having the porosity and pore size distribution described herein are ideally suited for use in metal ion battery anodes because they are suitable for forming dense electrode layers that are dispersible in slurries, structurally robust, retain capacity over repeated charge / discharge cycles, and have a uniform thickness in the conventional range of 20 μm to 50 μm.
[0114] The composite particles have a D of at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 It can have a particle size.
[0115] The composite particles have a D of 40 μm or less, or 30 μm or less, or 20 μm or less, or 15 μm or less, or 10 μm or less, or 8 μm or less, or 6 μm or less. 90 It can have a particle size.
[0116] The porous carbon skeleton in step (a) has a D of at least 30 μm. 50 The composite particles obtained in step (c) have a particle diameter of 20 μm or less D 50 It is preferred that the porous carbon skeleton in step (a) has a particle size D of at least 40 μm. 50 The composite particles obtained in step (c) have a particle diameter of 20 μm or less D 50 It is more preferred that the porous carbon skeleton in step (a) has a particle size D of at least 50 μm. 50 The composite particles obtained in step (c) have a particle diameter of 20 μm or less D 50 It is more preferable that the particle size is large.
[0117] The composite material of the present invention is preferably 300 mm 2 / g or less, or 250m 2 / g or less, or 200m 2 / g or less, or 150m 2 / g or less, or 100m 2 / g or less, or 80m 2 / g or less, or 60m 2 / g or less, or 40m 2 / g or less, or 30m 2 / g or less, or 25m 2 / g or less, or 20m 2 / g or less, or 15m 2 / g or less, or 10m 2 The BET surface area is preferably at least 0.1 m2 / g. Typically, a small BET surface area is preferred to minimize the formation of a solid electrolyte interfacial (SEI) layer on the surface of the composite particles during the first charge-discharge cycle of an anode comprising the particulate material of the present invention. However, an excessively small BET surface area leads to unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to metal ions in the surrounding electrolyte. For example, the BET surface area is preferably at least 0.1 m2 / g. 2 / g, or at least 1m 2 / g, or at least 2m 2 / g, or at least 5m 2 / g. For example, the BET surface area is 2 / g~25m 2 / g, more preferably 2m 2 / g~15m 2 / g range.
[0118] Preferably at least 90% by weight, more preferably at least 95% by weight, more preferably at least 98% by weight, more preferably at least 99% by weight of the electroactive mass in the composite particles is located within the interior pore volume of the porous carbon skeleton such that there is little or no electroactive material located on the outer surface of the composite particles.
[0119] The volume of micropores and mesopores in the composite particles (i.e., in the presence of the electroactive material), as measured by nitrogen gas adsorption, is preferably 0.15×P1 or less, or 0.10×P1 or less, or 0.05×P1 or less, or 0.02×P1 or less.
[0120] The weight ratio of the electroactive material, such as silicon, to the porous carbon skeleton in the composite particles can be determined by elemental analysis. Elemental analysis is used to determine the weight percentage of both the electroactive material and carbon in the composite particles. Optionally, the amount of hydrogen, nitrogen, and oxygen can also be determined by elemental analysis. Elemental analysis can be used to determine the weight percentage of the carbon ( It is also preferred to use the weight fraction of silicon (and optionally hydrogen, nitrogen, and oxygen) in the porous carbon skeleton. Determining the weight fraction of carbon in only the porous carbon skeleton allows for the possibility that the porous carbon skeleton may contain small amounts of heteroatoms in its molecular framework. By performing both measurements together, the weight fraction of silicon in the entire porous carbon skeleton can be reliably determined.
[0121] The electroactive material (e.g., silicon) content is preferably determined by ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy). Available from ThermoFisher Scientific Many ICP-OES instruments are commercially available, such as the iCAP™ 7000 series of ICP-OES analyzers. The carbon content (and optionally hydrogen, nitrogen, and oxygen content) in the composite particles and in the porous carbon skeleton alone is preferably determined by IR absorption. A suitable instrument for determining the carbon, hydrogen, nitrogen, and oxygen content is the TruSpec™ Micro elemental analyzer available from Leco Corporation.
[0122] Suitably, when the electroactive material is silicon the composite particles comprise between 30% and 80% by weight silicon, preferably between 45% and 65% by weight silicon.
[0123] The composite particles preferably have a low total oxygen content. Oxygen may be present in the composite particles, for example, as part of the porous carbon skeleton or as an oxide layer on any exposed silicon surface. The total oxygen content of the composite particles is preferably less than 15% by weight, more preferably less than 10% by weight, more preferably less than 5% by weight, for example less than 2% by weight, or less than 1% by weight, or less than 0.5% by weight.
[0124] When the electroactive material is silicon, the weight ratio of silicon to the porous carbon skeleton in the composite particles is preferably in the range of [0.5×P1 to 2.2×P1]: 1. This relationship defines a weight ratio of silicon such that about 20% to 95% by volume of the pore volume is occupied by silicon, taking into account the density of silicon and the pore volume of the porous carbon skeleton.
[0125] The composite particles typically have a specific charge capacity of 1200 mAh / g to 2340 mAh / g upon initial lithiation. The composite particles preferably have a specific charge capacity of at least 1400 mAh / g upon initial lithiation.
[0126] As mentioned above, certain classes of porous carbon scaffolds can be used to target certain classes of composite particle products. It will be understood that the pore structure of the porous carbon scaffolds, such as micropores and / or mesopores, is retained in the composite particle products. Certain classes of composite particle products are described below. It will be understood that the characteristics of the classes of composite particles described below should be considered in combination with the characteristics of the composite particles described above, such as particle size.
[0127] Composite particle 1 The composite particle 1 produced by the method of the present invention is (a) a porous carbon framework containing micropores and / or mesopores, Micropores and / or mesopores are defined as those with a total pore volume of Pcm as measured by gas adsorption. 3 / g, where P1 represents a natural number having a value of at least 0.7, and PD measured by gas adsorption 50 a porous carbon skeleton having pores with a diameter of 5 nm or less; (b) a plurality of elemental nanoscale silicon domains located within the micropores and / or mesopores of the porous carbon framework; Including, The weight ratio of silicon to the porous carbon skeleton in the composite particles is in the range of [0.5×P1 to 1.3×P1]:1. This is because the volume of silicon (in an uncharged state) is This corresponds to approximately 20% to 55% of the pore / mesopore volume.
[0128] The composite particle 1 can be produced using the porous carbon skeleton 1 as a starting material. Thus, the pore structure of the porous carbon skeleton 1 can be present in the composite particle 1.
[0129] The weight ratio of silicon to carbon is preferably in the range of [0.55×P1 to 1.1×P1]:1, or in the range of [0.6×P1 to 1.1×P1]:1, or in the range of [0.6×P1 to 1×P1]:1, or in the range of [0.6×P1 to 0.95×P1]:1, or in the range of [0.6×P1 to 0.9×P1]:1, or in the range of [0.65×P1 to 0.9×P1]:1, or in the range of [0.65×P1 to 0.85×P1]:1, or in the range of [0.65×P1 to 0.8×P1]:1, or in the range of [0.7×P1 to 0.8×P1]:1.
[0130] Silicon preferably occupies about 25% to about 45%, more preferably about 25% to 40% of the internal pore volume of the porous carbon skeleton. Within these preferred ranges, the pore volume of the porous carbon skeleton is effective to accommodate the expansion of silicon during charging and discharging, and excess pore volume that does not contribute to the volumetric capacity of the particulate material is avoided. However, the amount of silicon is also not so great as to prevent effective lithiation due to insufficient metal ion diffusion rate or insufficient expansion volume resulting in mechanical resistance to lithiation.
[0131] Composite particle 1 has a D range of 0.5 μm to 50 μm. 50It can have a particle size. 50 The particle size can optionally be less than 20 μm.
[0132] The composite particle 1 has a diameter of, for example, 1 μm to 25 μm, or 1 μm to 20 μm, or 2 μm to 20 μm, or 2 μm to 15 μm, or 3 μm to 15 μm. 50 It can have a particle size.
[0133] Composite particles 2 The composite particle 2 produced by the method of the present invention is (a) a porous carbon framework containing micropores and mesopores, (i) Micropores and mesopores have a total pore volume of Pcm as measured by gas adsorption. 3 / g, where P1 has a value of at least 0.6; (ii) The volume ratio of micropores to the total volume of micropores and mesopores (φ a ) is in the range of 0.1 to 0.9, (iii) The volume ratio of pores having a pore diameter of 20 nm or less to the total volume of micropores and mesopores (φ 20 ) is at least 0.75, and (iv) the porous carbon skeleton has a D of less than 20 μm 50 a porous carbon skeleton having a particle size; (b) a plurality of nanoscale elemental silicon domains located within the micropores and / or mesopores of the porous carbon framework; Including, The weight ratio of silicon to the porous carbon skeleton in the composite particle is in the range of [1×P1 to 2.2×P1]:1.
[0134] The composite particle 2 can be manufactured using the porous carbon skeleton 2 as a starting material. Thus, the pore structure of the porous carbon skeleton 2 can be present in the composite particle 2.
[0135] Composite particles 2 are particularly suitable for use in "hybrid" electrodes which include a combination of graphite and composite particles.
[0136] The weight ratio of silicon to the porous carbon skeleton in the composite particles is [1×P1~2.2× P1]:1. The weight ratio of [1 × P1]:1 corresponds to a density of silicon of approximately 2.3 g / cm 3 This corresponds to a silicon occupancy rate of the pores of the porous carbon skeleton of about 43 v / v %. The upper limit of the weight ratio [2.2 × P1]:1 corresponds to a silicon occupancy rate of the pores of the porous carbon skeleton of about 95 v / v %.
[0137] The weight ratio of silicon to the porous carbon skeleton is preferably at least 1.1 x P1, more preferably at least 1.15 x P1, more preferably at least 1.2 x P1, more preferably at least 1.25 x P1, more preferably at least 1.3 x P1, more preferably at least 1.35 x P1, more preferably at least 1.4 x P1.
[0138] When the porous carbon skeleton has a relatively high ratio of mesopores to micropores (e.g., φ a is in the range of 0.2 to 0.5, or in the range of 0.3 to 0.5), the weight ratio of silicon to carbon can be even higher, for example at least 1.45×P1, more preferably at least 1.5×P1, more preferably at least 1.55×P1, more preferably at least 1.6×P1, more preferably at least 1.65×P1, more preferably at least 1.5×P1.
[0139] In a further preferred embodiment, the minimum weight ratio of silicon to the porous carbon skeleton is at least [φ b +0.75] × P1, or at least [φ b +0.8] × P1, or at least [φ b +0.9] × P1, or at least [φ b +1]×P1, or at least [φ b +1.1] × P1. Therefore, the mesoporosity (φb ) has a higher value, the amount of silicon in the composite particle 2 is also higher. This correlation between mesoporosity and the minimum weight ratio of silicon to the porous carbon scaffold results in the porous carbon scaffold having a higher mesoporosity being occupied to a higher extent by silicon, thereby optimizing the volumetric capacity of the composite particle 2. The higher minimum loading of silicon in the porous carbon scaffold having a higher mesoporosity also reduces the possibility of larger micropores being partially occupied by silicon, thereby limiting the formation of undesirable SEI by reducing the silicon surface area exposed to the electrolyte.
[0140] In a further embodiment, the maximum weight ratio of silicon to the porous carbon skeleton is [φ b +1.6] × P1, and more preferably [φ b +1.5] × P1. This correlation between mesoporosity and the maximum weight ratio of the porous carbon scaffold ensures that porous carbon scaffolds with higher microporosity are not overfilled with silicon.
[0141] Composite particle 2 has a D range of 0.5 μm to 20 μm. 50 The composite particle 2 may have a particle diameter D 50 The particle size is preferably 12 μm or less, or 10 μm or less, or 8 μm or less.
[0142] The composite particle 2 has a diameter D in the range of, for example, 1 μm to 12 μm, or 1 μm to 10 μm, or 2 μm to 10 μm, or 3 μm to 8 μm. 50 It can have a particle size.
[0143] Composite particle 2D 10 The particle size is preferably at least 0.5 μm.
[0144] Composite particle 2D 90 The particle size is preferably 12 μm or less, or 10 μm or less.
[0145] Composite particles 3 The composite particle 3 produced by the method of the present invention is (a) a porous carbon framework containing micropores and / or mesopores, The micropores and mesopores have a total pore volume of at least 0.7 cm as measured by gas adsorption. 3 / g, PD measured by gas adsorption 50 a porous carbon skeleton having pores with a diameter of 2 nm or less; (b) an electroactive material located within the micropores and / or mesopores of the porous carbon framework; The composite particles have a D of 10 μm or less. 90 It has a particle size.
[0146] The composite particle 3 can be manufactured using the porous carbon skeleton 3 as a starting material. Thus, the pore structure of the porous carbon skeleton 3 can be present in the composite particle 3.
[0147] The composite particles 3 relate to particulate materials in which the porous carbon skeleton has a relatively high total volume of micropores and mesopores, with pores having a diameter of 2 nm or less constituting at least 50% of the total pore volume. This pore structure can be derived from the porous carbon skeleton 3. The composite particles 3 have a particle size distribution that is heavily biased towards particles with a diameter of 10 μm or less. It has been found that the combination of small particle size and highly divided pore volume provides an electroactive material that is highly resistant to mechanical degradation during electrode fabrication.
[0148] Composite particle 3D 90 The particle size is preferably 9.5 μm or less, or 9 μm or less, or 8.5 μm or less, or 8 μm or less, or 7.5 μm or less, or 7 μm or less, or 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less.
[0149] The composite particles 3 preferably have a diameter D in the range of 0.5 μm to 7 μm. 50 Particle size: D 50The particle size can optionally be at least 1 μm, or at least 1.5 μm, or at least 2 μm, or at least 2.5 μm, or at least 3 μm.
[0150] D 50 The particle size can optionally be 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less, or 3.5 μm or less.
[0151] The composite particle 3 has a diameter of, for example, 1 μm to 6.5 μm, or 1.5 μm to 6 μm, or 2 μm to 5.5 μm, or 2.5 μm to 5 μm, or 3 μm to 4.5 μm. 50 It can have a particle size.
[0152] Composite particle 3D 10 The particle size is preferably at least 0.5 μm.
[0153] Composite particle 3D 99 The particle size is preferably 25 μm or less.
[0154] The amount of electroactive material in the composite particle 3 is preferably selected such that the electroactive material occupies no more than about 55% of the internal pore volume of the porous carbon skeleton (in the uncharged state). The electroactive material preferably occupies about 25% to about 45% of the internal pore volume of the porous carbon skeleton, more preferably about 25% to 40% of the internal pore volume of the porous carbon skeleton.
[0155] When the electroactive material is silicon, the weight ratio of silicon to the porous carbon skeleton is preferably [0.5×P1 to 1.3×P1]: 1. The weight ratio of silicon to carbon is more preferably in the range of [0.55×P1 to 1.1×P1]: 1, or in the range of [0.6×P1 to 1.1×P1]: 1, or in the range of [0.6×P1 to 1×P1]: 1, or in the range of [0.6×P1 to 0.95×P1]: 1, or in the range of [0.6×P1 to 0.9×P1]: 1, or in the range of [0.65×P1 to 0.9×P1]: 1, or in the range of [0.65×P1 to 0.85×P1]: 1, or in the range of [0.65×P1 to 0.8×P1]: 1, or in the range of [0. The range is 7×P1~0.8×P1]:1.
[0156] Carbon Coating The method of the present invention may optionally include a further step comprising depositing a conductive coating, preferably a carbon-based coating, on the composite particles. Suitably, the conductive carbon-based coating may be obtained by a chemical vapor deposition (CVD) process. CVD is a methodology known in the art and involves pyrolysis of a volatile carbon-containing gas (e.g., ethylene) on the surface of the particulate material. Alternatively, the carbon-based coating may be formed by depositing a solution of a carbon-containing compound on the surface of the particulate material, followed by pyrolysis. The conductive coating (such as a carbon-based coating) has sufficient permeability to allow lithium access to the interior of the composite particle without excessive resistance so as not to degrade the rate performance of the composite particle. For example, the thickness of the conductive coating may suitably be in the range of 2 nm to 30 nm. The conductive coating may optionally be porous and / or may only partially cover the surface of the composite particle.
[0157] The conductive coating smoothes out any surface imperfections and reduces the remaining microporosity of the surface. ) has the advantage of further reducing the BET surface area of the composite particles, thereby further reducing first cycle losses. The conductive coating also improves the conductivity of the surface of the composite particles, reducing the need for conductive additives in the electrode composition, and provides an optimal surface for the formation of a stable SEI layer, improving capacity retention upon cycling.
[0158] The BET surface area of the composite particles after deposition of the conductive coating is preferably greater than 50 m 2 / g, less than 30m 2 / g, less than 20m 2 / g, more preferably less than 10m 2 / g or less than 5m 2 / g.
[0159] Product end use The method of the present invention can optionally include the further step of forming an electrode composition comprising the composite particles, where the composite particles are optionally coated with a conductive carbon coating. The electrode composition can include at least one other component selected from (i) a binder, (ii) a conductive additive, and (iii) an additional particulate electroactive material.
[0160] The method of the present invention can optionally include the further step of forming a slurry comprising the composite particles (wherein the composite particles are optionally coated with a conductive carbon coating) and a solvent.
[0161] Product by Process The present invention also provides particulate materials comprising composite particles obtainable by the method of the present invention. The nanostructure of electroactive materials deposited by the CVI process of the present invention is different from the nanostructure of electroactive materials deposited by other means. And because the composite particles result from the CVI process and a subsequent grinding process, they can be distinguished from particles of similar size made without a subsequent grinding step. For example, the grinding step produces a fracture surface that can be observed by a microscope. Thus, the composite particles obtainable by the method of the present invention can be distinguished from composite particles obtained by other means. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0162] Silicon-carbon composite particles were synthesized in a vertical bubbling fluidized bed reactor equipped with a stainless steel cylindrical vessel with an inner diameter of 83 mm. 2 / g, total pore volume 0.78 cm 3 / g, P.D. 10 0.97nm, PD 50 1.15nm, PD 90 is 2.23 nm, and φ a 126 g of a premix of porous carbon particles with a molecular weight of 61% is placed in the reactor. Inert gas (nitrogen) is injected into the reactor at a low flow rate to remove oxygen. The reactor is then heated to 420°C. The reactor was heated to a reaction temperature of 40° C. and 1.25% v / v monosilane gas diluted with nitrogen was fed into the bottom of the reactor at a flow rate sufficient to fluidize the carbon skeleton particles for 32.3 hours (sample 1) or 37 hours (sample 2). Upon completion of the reaction period, the reactor atmosphere was switched to pure nitrogen while maintaining fluidization, and this purge was continued for 30 minutes. The furnace was then allowed to warm to ambient temperature over several hours. After reaching ambient temperature, the furnace atmosphere was gradually switched to air over several hours.
[0163] The product was added to the feed tray of an MC DecJet™ 30 mill and milling was carried out in an inert atmosphere. The ring pressure was set at 650 kPa and the venturi pressure was set at 700 kPa. The product was pulverized and then collected in a suitable container. The material properties of the two composites are shown in Table 1.
[0164] [Table 1]
[0165] Preparation of the negative electrode Negative electrode coatings (anodes) were made from the materials of Sample 1 and Sample 2. A dispersion of carbon black Super P™ (conductive carbon) in CMC binder was mixed in a Thinky™ mixer. The Si-C composite was added to the mixture and mixed in the Thinky™ mixer for 30 minutes. SBR binder was then added to achieve a 1:1 CMC:SBR ratio to obtain a slurry with a Si-C composite:CMC / SBR:carbon black weight ratio of 70%:16%:14%. The slurry was mixed in the Thinky™ mixer for an additional 30 minutes and then coated onto a 10 μm thick copper substrate (current collector) and dried at 50° C. for 10 minutes, followed by further drying at 110° C. for 12 hours to form the negative electrode.
[0166] Cell Manufacturing and Cycle Full cell manufacturing A full coin cell was fabricated using a circular anode with a radius of 0.8 cm cut from the coating formed from Samples 1 and 2 (described above), a porous polyethylene separator, and a nickel manganese cobalt (NMC532) cathode. The cathode and anode were designed to form a balanced pair such that the capacity ratio of the cathode to the anode was 0.9. An electrolyte consisting of 1M LiPF6 in a 7:3 EMC / FEC (ethylene methyl carbonate / fluoroethylene carbonate) solution containing 3 wt% vinylene carbonate was then added to the cell before sealing.
[0167] The full coin cell was cycled as follows: The anode was lithiated by applying a constant current at a rate of C / 25 with a cutoff voltage of 4.3 V. Once the cutoff voltage was reached, a constant voltage of 4.3 V was applied until a cutoff current of C / 100 was reached. The cell was then allowed to rest for 10 minutes in the lithiated state. The anode was then delithiated at a constant current of C / 25 with a cutoff voltage of 2.75 V. The cell was then allowed to rest for 10 minutes. After this initial cycle, the anode was lithiated at a constant current of C / 2 with a cutoff voltage of 4.3 V, followed by a constant voltage of 4.3 V with a cutoff current of C / 40 and a rest time of 5 minutes. The anode was then delithiated at a constant current of C / 2 with a cutoff voltage of 2.75 V. This was then repeated for the desired number of cycles.
[0168] The charge (lithiation) and discharge (delithiation) capacities for each cycle are calculated per unit mass of silicon-carbon composite, and the capacity retention is calculated for each discharge capacity as a percentage of the second cycle discharge capacity. The first cycle loss (FCL) is (1-(first delithiation capacity / first lithiation capacity)) x 100%. Key values averaged across three coin cells for each material are shown in Table 2.
[0169] [Table 2]
Claims
1. (a) containing micropores and / or mesopores and having a D of at least 20 μm 50 Providing a particulate porous carbon skeleton having a particle size; (b) depositing an electroactive material selected from silicon, tin, aluminum, germanium, and alloys thereof into the micropores and / or mesopores of the porous carbon framework using a chemical vapor infiltration process in a fluidized bed reactor to obtain intermediate particles; (c) grinding the intermediate particles to obtain composite particles; A method for making a composite particle, comprising:
2. The method of claim 1 further comprising, prior to step (c), transferring the intermediate particles to a grinding device.
3. The method of claim 1 or 2, wherein the electroactive material is silicon.
4. 4. The method of claim 1, wherein the intermediate particles and the composite particles comprise a plurality of nanoscale domains of the electroactive material in elemental form located within the micropores and / or mesopores of the porous carbon framework.
5. 5. The method according to any one of claims 1 to 4, wherein the chemical vapor infiltration process is carried out at a temperature in the range of 200°C to 1250°C, or 400°C to 700°C, or 450°C to 550°C, or 450°C to 500°C.
6. 6. The method according to any one of claims 1 to 5, further comprising the step of cooling the intermediate particles before grinding them, optionally wherein the cooling is to a temperature below 100°C or below 50°C, or to ambient temperature.
7. 7. The method according to any one of claims 1 to 6, further comprising the step of passivating the intermediate particles before grinding them, wherein, optionally, the passivation is carried out in an inert gas or in an environment having an oxygen concentration of less than 10% by volume.
8. The method according to any one of claims 1 to 7, wherein the grinding device is a jet mill.
9. The method according to any one of claims 1 to 8, wherein the step of grinding the intermediate particles is carried out in an inert gas or in an environment having an oxygen concentration of less than 10% by volume.
10. The process according to any one of claims 1 to 9, which is a continuous or batch process.
11. The micropores and / or mesopores of the porous carbon skeleton have a total pore volume of P 1 cm 3 / g, where P 1 11. The method of any one of claims 1 to 10, wherein x has a value of at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.
2.
12. The micropores and / or mesopores of the porous carbon skeleton have a total pore volume of P 1 cm 3 / g, where P 1 12. The method of any one of claims 1 to 11, wherein R has a value of 2.5 or less, or 2.2 or less, or 2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less.
13. The micropores and / or mesopores of the porous carbon skeleton have a total pore volume of P 1 cm 3 / g, where P 1 The method of claim 12, wherein the value of is in the range of 0.4 to 2.5, or in the range of 0.6 to 2.5, or in the range of 0.7 to 2, or in the range of 0.7 to 1.
2.
14. The porous carbon skeleton has a D in the range of 60 μm to 150 μm. 50 The method according to any one of claims 1 to 13, wherein the particle size is 0.01 to 0.
1.
15. The porous carbon skeleton has a D of at least 30 μm, or at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm, or at least 80 μm. 50 The method according to any one of claims 1 to 14, wherein the particle size is 0.01 to 0.
1.
16. The porous carbon skeleton has a D of 1000 μm or less, or 500 μm or less, or 250 μm or less, or 150 μm or less. 50 The method according to any one of claims 1 to 15, wherein the particle size is 0.01 to 0.
1.
17. The porous carbon skeleton has a D of at least 5 μm, or at least 15 μm, or at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm. 10 The method according to any one of claims 1 to 16, wherein the particle size is 0.01 to 0.
1.
18. The porous carbon skeleton has a D of 1500 μm or less, or 1000 μm or less, or 750 μm or less, or 500 μm or less, or 200 μm or less. 90 The method according to any one of claims 1 to 17, wherein the particle size is 0.01 to 0.
1.
19. The porous carbon skeleton has a D of 1550 μm or less, or 1050 μm or less, or 800 μm or less, or 550 μm or less, or 250 μm or less. 98 The method according to any one of claims 1 to 18, wherein the particle size is 0.01 to 0.
1.
20. The porous carbon skeleton is at least 750 mm 2 / g, or at least 1000m 2 / g, or at least 1250 m 2 / g, or at least 1500m 2 The method according to any one of claims 1 to 19, wherein the SiO2 has a BET surface area of 0.1 to 0.5 g / g.
21. The porous carbon skeleton is 4000m 2 / g or less, or 3500m 2 / g or less, or 3250m 2 / g or less, or 3000m 2 The method according to any one of claims 1 to 20, wherein the SiO2 has a BET surface area of 0.1 to 0.5 g / g or less.
22. The porous carbon skeleton is 1500 mm 2 / g to 3000m 2 22. The method of claim 21 , wherein the SiO 2 has a BET surface area of 100 / g.
23. The porous carbon skeleton has a PD 50 23. The method of any one of claims 1 to 22, wherein the pore size is 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less, or 1.5 nm or less, or 1 nm or less.
24. The composite particles have a D in the range of 0.5 μm to 20 μm. 50 The method according to any one of claims 1 to 23, wherein the particle size is 0.01 to 0.
25.
25. The composite particles have a D of at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. 50 The method of claim 24, wherein the particle size is
26. The composite particles have a D of 20 μm or less, or 15 μm or less, or 12 μm or less, or 10 μm or less, or 9 μm or less, or 8 μm or less, or 7 μm or less, or 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less, or 3.5 μm or less. 50 26. The method of claim 24 or 25, wherein the particle size is
27. The composite particles have a D of at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 The method according to any one of claims 1 to 26, wherein the particle size is 0.01 to 0.25
28. The composite particles have a D of 80 μm or less, or 60 μm or less, or 40 μm or less, or 30 μm or less, or 25 μm or less, or 20 μm or less, or 10 μm or less. 90 The method according to any one of claims 1 to 27, wherein the particle size is 0.01 to 0.
25.
29. 29. The method of any one of claims 1 to 28, wherein the composite particles have a particle size distribution span of 5 or less, or 4 or less, or 3 or less, or 2 or less, or 1.5 or less.
30. The electroactive material is silicon and the pore volume of the composite particle is P 1 cm 3 / g, and the weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.5×P 1 ~2.2 x P 1 ]: range of 1, or [1 x P 1 ~2.2 x P 1 ]: range of 1, or [0.5 × P 1 ~1.3 x P 1 30. The method of any one of claims 1 to 29, wherein the ratio of 1 to 1 is in the range of .
31. A method according to any one of the preceding claims, wherein the electroactive material is silicon and the composite particles comprise from 30% to 80% by weight silicon, or from 45% to 65% by weight silicon.
32. The method of any one of claims 1 to 31, wherein the composite particles comprise no more than 15% by weight oxygen, or no more than 10% by weight oxygen.
33. A particulate material comprising composite particles obtainable by the method according to any one of claims 1 to 32.
Citation Information
Patent Citations
Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof
WO2017040299A1
Decomposition of silicon-containing precursors on porous scaffold materials
WO2018165610A1
Lithium secondary battery
JP2003100284A